1968
DOI: 10.1097/00006842-196807000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal Arousal of Chronically Ill Psychiatric Patients Undergoing Intensive Behavioral Treatment

Abstract: Severely regressed female psychiatric patients were tested repeatedly while undergoing an intensive behavioral treatment program. The study focuses on interrelations between some of the physiological and overt behavioral measures taken during the course of therapy. In the initial testing, severity of illness, which was evaluated from the patient's behavior, was found to be negatively related to basal skin conductance level, and to spontaneous and specific GSR activity. The longitudinal data collected over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Furthermore, using a variety of rating scales, several other laboratories have also identified a subgroup of patients marked by both emotional withdrawal and conceptual disorganization, and noted them to be strikingly deficient across a wide range of functions. Using the Psychotic Reaction Profile, Fenz and Steffy (1968) reported electrodermal nonresponsiveness among chronic female psychiatric patients was associated with cognitive disorganization and emotional withdrawal. Franzen and Ingvar (1975 a , 1975 b ) found altered cerebral blood flow was most striking in patients displaying the greatest emotional withdrawal and cognitive disorganization, as rated by the Rockland-Pollin scale.…”
Section: Negative Symptoms and Or Nonresponding Or Is There A Specifi...mentioning
confidence: 99%
“…Furthermore, using a variety of rating scales, several other laboratories have also identified a subgroup of patients marked by both emotional withdrawal and conceptual disorganization, and noted them to be strikingly deficient across a wide range of functions. Using the Psychotic Reaction Profile, Fenz and Steffy (1968) reported electrodermal nonresponsiveness among chronic female psychiatric patients was associated with cognitive disorganization and emotional withdrawal. Franzen and Ingvar (1975 a , 1975 b ) found altered cerebral blood flow was most striking in patients displaying the greatest emotional withdrawal and cognitive disorganization, as rated by the Rockland-Pollin scale.…”
Section: Negative Symptoms and Or Nonresponding Or Is There A Specifi...mentioning
confidence: 99%
“…In addition to changing social behavior, decreasing the frequency of aggressive behavior has been an important goal. Steffy and his associates (Fenz and Steffy, 1968;Steffy, unpublished;Steffy et al, 1969) described a program to deal with both aggressive and regressed female in-patients. As part of this program (Steffy, unpublished), individual contracts were made and negotiated with each patient to help bring her aggressive behavior under control.…”
Section: Psychiatric Inpatientsmentioning
confidence: 99%
“…Venables and Wing (1962) came to similar conclusions using skin potential as their autonomic measure; they found that the more socially withdrawn the schizophrenic, the greater was his level of "arousal." Wing (1964) reported the opposite for reactivity on the GSR; similarly, Fenz and Steffy (1968) found severity of illness in a group of schizoprenic women to be negatively related to basal conductance and to spontaneous and specific GSR activity. Thus, level of arousal by itself does not seem to be a comprehensive term to describe a schizophrenic patient.…”
Section: Discussionmentioning
confidence: 92%